Citizen Intellectuals in Historical Perspective: Reflections on Callahan's "Citizen Ai". Issue 4 (20th November 2014) - Cheek, Timothy
<x content-type="archive" xml:space="preserve">Abstract</x> William Callahan's conceptualization of Ai Weiwei as a "citizen intellectual" is the latest in a long-standing cottage industry seeking to make sense of and define China's intellectuals. Frederic Wakeman Jr. in 1972 offered "a typology of intellectual species" for Chinese thinkers and writers in late imperial China: statesman, administrator, ethical idealist, aesthete, and emirite or recluse (Wakeman 1972, 35). Hao Zhidong applies a Weberian lens on twentieth-century Chinese intellectuals to identify nested categories of: professional, cultural, and (smallest of all) critical intellectuals (Hao 2003, 393). Tani Barlow traces the identity of China's thinkers and writers from "intellectual class" in 1905 to "enlightened scholars" in the 1920s to "intellectual" (zhishifenzi) ever since. Barlow identifies a tension between the social power of these knowledge specialists and their dangerous dance with the state in which they succumbed under both Nationalist and Communist regimes to a service role to power, a "category of the state" (Barlow 1991, 216). Merle Goldman has focused on critical intellectuals under the Chinese Communist Party, what most people think of as critics and dissidents. Carol Hamrin and I sought to go beyond Goldman's focus on dissidents to study "establishment intellectuals" by looking at "the motives and means for collaboration, as well as the sources of tension and conflict between leading intellectuals and the top Communist Party leadership" (Hamrin and Cheek 1986, 3). "Establishment intellectual" proved a useful category for opening up our understanding of intellectual participation at the elite level under Mao and during the 1980s. The 1989 Tiananmen demonstrations and the June 4th massacre and crackdown changed everything. Merle Goldman usefully picked up on these changes by identifying the rise of "disestablished intellectuals" in the post-Tiananmen period, particularly intellectuals who had been active in the reformist administration of the CCP in the 1980s associated with disgraced General Secretary Hu Yaobang (Goldman 2007, 15ff, 86ff). These fallen establishment intellectuals populated the academic posts, publishing ventures, and new business opportunities that exploded after Deng Xiaoping's famous certification of economic reform in his 1992 "Southern Tour."